IMPROVING THE UNDERSTANDING OF CONCEPTS OF MOMENTUM AND IMPULS OF STUDENTS BY IMPLEMENTATION OF EVIDENCE BASED LEARNING MODELS IN CLASS X SENIOR HIGH SCHOOL - Ullya Muflihatin; Nur Islami; Fakhruddin Z (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
This research aims to describe and find out the increase in students' understanding of concepts in the indicators of translation, interpretation, and extrapolation in class X SMA 9 Pekanbaru by applying evidence based learning (EBL) learning models to the momentum and impulse material. This type of research is a quasi experimental. The research population was students of class X SMA 9 Pekanbaru in the Academic Year 2018/2019. The research sample consisted of 2 classes totaling 72 students, of which the experimental class X IPA3 and the control class X IPA6. Research data based on posttest scores understanding the concept of momentum and impulse material, obtained after the implementation of the learning model is given. Data were analyzed descriptively and inferentially to see an increase in students' understanding of concepts. The results of data analysis obtained an increase in students' understanding of the concept of class X IPA3 reaching 71.73% with the category of understanding the average concept is good, while the results of inferential analysis, there is a significant increase in understanding of the concept of momentum and impulse material. Thus, the application of evidence based learning models is effective in increasing students' understanding of concepts in the material momentum and impulses in class X3 SMA 9 Pekanbaru.